Description of The Health Condition of Indonesian Soldiers 1st Infantry Division Kostrad Cilodong - Arfiyanti, Arfiyanti; Hayati, Taureni; Widuri, Lila Irawati Tjahjo; Rachman, Arief; Dewi, Dian Andriani Ratna; Aziz, Abdul (Eduvest - Journal of Universal Studies, 2023)
Community service aims to determine the health picture of Indonesian soldiers in the 1st Infantry Division of Kostrad Cilodong. Therefore, researchers conduct general health screening by measuring body mass index, blood pressure, and glucose levels in the blood. This study used a descriptive method. This method describes a subject or object under study in depth, detail, and breadth. This study used two types of data: primary and secondary. The results of community service as a whole, when viewed from blood pressure measurement data and glucose levels in the blood, can be said to be normal. The routine of Indonesian soldiers is like regular exercise, a healthy and stable diet, and adequate rest influences to reduce risk factors for diabetes mellitus.